Effect of disodium EDTA chelation regimen on cardiovascular events in patients with previous myocardial infarction: The TACT Randomized Trial - Lamas, Gervasio A. (2013)
CONTEXT: Chelation therapy with disodium ethylene diamine tetraacetic acid (EDTA) has been used for over 50 years to treat atherosclerosis without proof of efficacy. OBJECTIVE: To determine if an EDTA-based chelation regimen reduces cardiovascular events. DESIGN AND SETTING: Double-blind placebo-controlled 2×2 factorial multicenter randomized trial. NIH Funding was approved in August 2002. The first patient was enrolled in September 2003, and the last follow-up took place in October 2011. Median follow-up was 55 months. Participants were recruited from 134 US and Canadian clinical sites. PARTICIPANTS: 1708 patients, age 50 or older and at least 6 weeks post myocardial infarction, with a serum creatinine <2.0 mg/dL. 289 patients (17% of total; 115 in the EDTA group and 174 in the placebo group) withdrew consent for continued follow-up over the course of the trial. INTERVENTIONS: Patients were randomized to receive 40 infusions of a 500 mL chelation solution (containing 3 grams of disodium EDTA, 7 grams of ascorbate, B-vitamins, electrolytes, procaine, and heparin) versus placebo, and to an oral vitamin and mineral regimen or an oral placebo. Infusions were administered weekly for 30 weeks, followed by 10 infusions 2 to 8 weeks apart. Patients received 55,222 infusions. 15% discontinued infusions for adverse events. MAIN OUTCOME MEASURE: The pre-specified primary endpoint was a composite of total mortality, recurrent myocardial infarction, stroke, coronary revascularization, or hospitalization for angina. Followup for clinical events began upon randomization. This report describes the intent-to-treat comparison of EDTA chelation versus placebo. To account for multiple interim analyses, the significance threshold required at the final analysis was p=0.036. RESULTS: The qualifying myocardial infarction occurred a median of 4.6 years before enrollment. Median age was 65 years, 18% were female, 9% were nonwhite, 31% were diabetic. 83% had prior coronary revascularization, and 73% were on statins. The primary endpoint occurred in 222 (26%) of the chelation group and 261 (30%) of the placebo group (hazard ratio 0.82, 95% confidence interval 0.69–0.99, p=0.035). There was no effect on total mortality (chelation: 87 deaths (10%) placebo 93 (11%): hazard ratio (HR) 0.93, 95% confidence interval 0.70–1.25, p=0.64), but the study was not powered for this comparison. The effect of EDTA chelation on the components of the primary endpoint other than death was of similar magnitude as its overall effect (myocardial infarction HR 0.77 95% confidence interval (0.54,1.11); stroke HR 0.77 95% confidence interval (0.34, 1.76); coronary revascularization HR 0.81 95% confidence interval (0.64, 1.02); hospitalization for angina HR 0.72 95% confidence interval (0.35, 1.47). Extensive sensitivity analyses examining the effect of patient drop out and varying treatment compliance did not alter the study’s conclusions. CONCLUSIONS AND RELEVANCE: In stable patients with a history of MI, the use of an intravenous chelation regimen with disodium EDTA, compared with placebo, modestly reduced the risk of a composite of adverse cardiovascular outcomes, many of which were revascularization procedures. These results provide evidence to guide further research but are not, by themselves, sufficient to support the routine use of chelation therapy for treatment of post-MI patients.